Prevalence of intestinal parasites among members of the public in Kuala Lumpur, Malaysia - Jamaiah, I.; Rohela, M. (SEAMEO Regional Tropical Medicine and Public Health Network, 2005)
A total of 246 stool samples were collected from the public who participated in a Medical Fair held at the University Malaya Medical Center. The stools were examined for intestinal parasites using the formalin-ether concentration technique. The overall infection rate was 6.9 (17 out of 246), with Trichuris trichiura being the most common parasite (4.5), followed by Ascaris lumbricoides (0.8), Clonorchis sinensis (0.8), hookworm (0.4), and Entamoeba histolytica (0.4). None of these participants showed any clinical symptoms. The highest infection rate was among the Chinese 7.7 (13 out of 169), followed by the Malays 7.0 (3 out of 43) and Indians 3.3 (1 out of 30). The highest infection rate was in the age group 16-30 years, which was 9 (6 out of 67). The two cases of clonorchiasis were from two Chinese women aged 28 and 66 years. The 28-year-old Chinese woman was born in Malaysia and had never left the country, while the older woman was also born in Malaysia but had visited Hong Kong as a tourist on two occasions. Both enjoyed eating raw fresh water fish with porridge.